CYTOKINE RECEPTORS OF BLOOD LYMPHOCYTES IN CHILDREN WITH BRONCHIAL ASTHMA - I.A. Gromov (Педиатрическая фармакология, 2006)
Blood lymphocyte membrane receptors to IFNγ, IL 2, IL 4, IL 5, IL 8 and IL 10 have been investigated to assess cytokine sensitivity variations in children with asthma. Thirty children aged 5–17 with remission of atopic bronchial asthma ranging from mild to moderate persistent formed the study group. Ten children without any atopic disorders formed the group of controls. The flow cytometry with direct reaction of monoclonal antibodies to the mentioned above cytokine receptors has been used. An increased expression of IL 2 (due to high affinity CD122 subunit) and IL 5 receptors has been registered in children with asthma, and so a numbers of cells bearing IL 4 and IL 8 receptors that has trended to be higher. At the same time, there has been a decrease of IFNγ receptor expression an a trend to lower expression of IL 10 receptor in these children.Key words: bronchial asthma, children, interferon-γ, interleukins.